Efficacy and Safety of Ablative Fractional Laser-Assisted Delivery of Methotrexate in Adults with Localized Scleroderma: A Randomized and Controlled Clinical Trial - Qing Guo; Mingjie He; Junjie Cen; Danqi Huang; Shaoyun Hao; Zengqi Tang; Hui Xiong (MDPI AG, 2022)
Localized scleroderma (LS) is an autoimmune disease with sclerosis of the skin as the main manifestation. Currently, there is no specific treatment for LS. The effectiveness of ablative fractional laser (AFL) therapy for LS has been demonstrated in several studies. Combining ablative fractional Er:YAG laser therapy with topical methotrexate may yield therapeutic benefits for patients with LS. To compare the efficacy and safety of AFL-assisted delivery of methotrexate in adults with LS, we randomly divided patients into an AFL therapy group and an ablative fractional laser-assisted delivery of methotrexate (AFL+MTX) therapy group. Laser and assisted drug delivery treatment were given every four weeks for four months, and 22 patients completed the trial. Ultrasound measurements of dermal thickness and histological fibrosis degree and the Localized Scleroderma Cutaneous Assessment Tool (LoSCAT) score were used to assess therapeutic effects. Treatment results showed that both AFL and AFL-assisted methotrexate delivery were effective in treating LS, and the laser combined with methotrexate therapy was more effective in improving clinical appearance (p value = 0.042) and dermal thickness (p value = 0.016). No serious adverse reaction occurred in either group. In conclusion, AFL and assisted delivery of methotrexate are effective and safe treatments for LS.